2007
DOI: 10.1007/s00442-007-0745-8
|View full text |Cite
|
Sign up to set email alerts
|

Linking water uptake with rooting patterns in grassland species

Abstract: Water availability strongly governs grassland primary productivity, yet this resource varies dramatically in time (seasonally) and space (with soil depth and topography). It has long been assumed that co-occurring species differ in their partitioning of water use by depth, but direct evidence is lacking. We report data from two growing seasons (2004-2005) in which we measured the isotopic signature of plant xylem water from seven species (including C(3) forbs and shrubs and C(4) grasses) growing along a topogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
192
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 211 publications
(214 citation statements)
references
References 43 publications
16
192
5
Order By: Relevance
“…Root biomass plays a vital role in the decomposition of SOM and helps in the formation of soil aggregates [10,45,60]. Generally, the study observations showed that animal grazing, the regular use of farm machinery, and several anthropogenic activities were assumed to be the reasons for low root biomass production in the CAO, Clm, and Clw; similar findings were observed by many researchers in their studies [62][63][64]. …”
Section: Effects Of Root Biomass In the Different Land-use Systemssupporting
confidence: 74%
“…Root biomass plays a vital role in the decomposition of SOM and helps in the formation of soil aggregates [10,45,60]. Generally, the study observations showed that animal grazing, the regular use of farm machinery, and several anthropogenic activities were assumed to be the reasons for low root biomass production in the CAO, Clm, and Clw; similar findings were observed by many researchers in their studies [62][63][64]. …”
Section: Effects Of Root Biomass In the Different Land-use Systemssupporting
confidence: 74%
“…However, these and other mechanisms have been found to have a minimal impact on encroachment of tallgrass prairie (Briggs et al 2005, McKinley andBlair 2008). Instead, the nature of feedbacks in tallgrass prairie may involve factors that structure mesic grasslands: pronounced belowground competition in the upper soil layers (Nippert and Knapp 2007a, b), frequent and intense fires (Knapp et al 1998, van Wilgen et al 2003, Briggs et al 2005, Bond 2008) and predominance of clonal reproduction (Benson andHartnett 2006, Dalgleish and.…”
Section: Introductionmentioning
confidence: 99%
“…18 O, À37% for dD [Nippert and Knapp 2007]). At this point on the MWL, the isotopic composition of water from fecal samples deviated from the MWL (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Water was extracted from fecal samples using cryogenic vacuum distillation (Nippert and Knapp 2007) using an extraction line operated in the Stable Isotope Mass Spectrometry Laboratory at KSU. Water samples from bison, rainfall, and stream-water were analyzed for their stable isotopic composition using a Picarro WS-CRDS isotopic water analyzer using ChemCorrect software to identify possible interference or sample contamination.…”
Section: Isotopic Analysismentioning
confidence: 99%